Relationship between serum cystatin-C and urinary neutrophil gelatinase-associated lipocalin in septic children - Jose Mandei; Elisa Iskandar; Adrian Umboh; Hesti Lestari (Indonesian Pediatric Society Publishing House, 2015)
Background Sepsis may lead to acute kidney injury (AKI) in patients treated in pediatric intensive care units (PICU). Currently, serum creatinine is used as a biomarker for the diagnosis of AKI. However, it is not a sensitive nor specific test for AKI. The scarcity of biomarkers leads to delays in the diagnosis and treatment of AKI. Serum cystatin-C (sCys-C) and urinary neutrophil gelatinase-associated lipocalin (uNGAL) are potential biomarkers that look promising for early diagnosis of AKI. Objective To identify the relation of cystatin-C and NGAL in children with sepsis. Methods Serum cystatin-C and uNGAL were measured on septic patients aged one month to 12 years. The diagnoses of sepsis were based on the 2002 International Pediatric Sepsis Concensus. Patients were admitted to the Pediatric Intensive Department of the Prof. Dr. R. D. Kandou Hospital, Manado from January to June 2013. The exclusion criteria were patients with trauma, burns, severe dehydration, malnutrition, obesity, and history of renal diseases. Data analyses included descriptions for the characteristic data and Pearson's coefficient correlation. A P value of 0.05 was considered to be statistically significant. Data were analyzed with SPSS software for Windows version 21. Results Thirty-eight patients met the inclusion criteria, of whom 23 were male and 15 were female. Their mean age was 22.6 (SD 32.24) months, with overweight in 2 children, good nutrition in 25 children, and under nutrition in 11 children. An increased level of sCys-C was found in 22 children and an increased level of uNGAL was found in 19 children. Serum cystatin-C was significantly correlated to uNGAL in septic patients (r=0.614; P<0.01). Conclusion There is a positively correlated relationship between sCys C and uNGAL in septic children. Increased sCys C is associated with increased uNGAL in septic children.